Calcium vanadate sub-microfibers as highly reversible host cathode material for aqueous zinc-ion batteries. Issue 16 (8th January 2019) - Liu, Xu; Zhang, Huang; Geiger, Dorin; Han, Jin; Varzi, Alberto; Kaiser, Ute; Moretti, Arianna; Passerini, Stefano
Abstract : CaV6 O16 ·3H2 O sub-microfibers were synthesized and investigated as highly reversible cathodes for aqueous Zn storage. Abstract : For the first time, CaV6 O16 ·3H2 O (CVO), synthesized via a highly efficient and fast microwave reaction, is used as a cathode material for aqueous zinc-ion batteries. Ex situ X-ray diffraction confirms the structure of this material to be stable upon reversible Zn 2+ intercalation, due to its large interlayer distance (8.08 Å). The pillaring effect of calcium makes the as-prepared CVO an excellent Zn 2+ cation host.